A Influence of Population Human Development Index and Unemployment Open to Poverty in Central Java - Putri, Lara Aziza (Rangkiang: Journal of Islamic Economics and Business, 2025)
This study aims to examine the influence of population, human development index (HDI), and open unemployment rate on poverty levels in ten selected districts of Central Java Province during the period of 2018–2022. Poverty remains a critical socioeconomic issue in Indonesia, especially in rural and semi-urban regions, where disparities in population distribution, human capital, and employment opportunities persist. The study adopts a quantitative approach using panel data regression analysis to investigate the determinants of poverty. Data were collected from the Central Bureau of Statistics (BPS) of Indonesia, encompassing annual figures on population, HDI, unemployment, and poverty rates in each district. The findings of the study reveal that the population variable has a statistically significant effect on poverty indicating that an increase in population size is associated with a rise in poverty rates, likely due to increased pressure on limited resources. Moreover, the human development index shows a significant negative effect on poverty, suggesting that improved education, health, and income levels contribute to poverty reduction. Conversely, the open unemployment rate demonstrates a significant positive impact on poverty, highlighting the critical role of labor market dynamics in influencing household welfare..